Spider Web, Integration-Interconnection Perspective Amin Abdullah - Haidar, Putri Bayu; Dzulfahmi, A. Adib (DAYAH: Journal of Islamic Education, 2024)
The troublesome contradiction between science and religion, which originated during the Renaissance and was introduced to Indonesia during the colonial era, marked the beginning of the formation of scientific integration. The answer proposed by several colleges is the merger of science and religion in the realm of education. It is envisioned that scientific viewpoints would no longer be independent and open as a result of scientific integration. The purpose of this research is to learn about the idea and execution of Islam and science integration at UIN Sunan Kalijaga Yogyakarta. This study employs a descriptive qualitative methodology in conjunction with a library research strategy. According to the findings of the study, the notion of Islam and science integration at UIN Sunan Kalijaga Yogyakarta is an interconnected integration strategy espoused by Amin Abdullah in the concept of scientific integration Spider's Web. The implementation has reached the level of systematic integrative scientific development, beginning with the philosophical level and progressing to the operational level of curriculum preparation and learning processes, or the strategic level.